1985
DOI: 10.1002/ajmg.1320200204
|View full text |Cite
|
Sign up to set email alerts
|

Transmitting balanced translocation carrier information within families: A follow‐up study

Abstract: Approximately 1 of 500 individuals is a carrier of a balanced chromosome translocation. Since many translocations are inherited, many (but not all) relatives of carriers have a need to be informed of their potential carrier status. Presently, no data are available as to what extent individuals identified as balanced carriers inform at-risk relatives of the problem. We interviewed 12 balanced translocation carriers to learn whether such information had been transmitted to relatives. The 12 propositi had 36 surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 2 publications
2
22
1
1
Order By: Relevance
“…In relation to telling second and third degree relatives our research supports other work (Suslak et al 1985, van Rijn et al 1997, Julian-Reynier et al 2000, Hughes et al 2002, Claes et al 2003 in that participants were more selective about who they told, mainly choosing to disclose to family members they felt emotionally close to or had some contact with. For example, one woman felt a particular responsibility to tell a certain cousin about the newly discovered risk of HD in their family, and although she was viewed as 'outside of the [close] family' she clearly felt some obligation to her:…”
Section: Theme 3: Who Is Family?supporting
confidence: 86%
See 2 more Smart Citations
“…In relation to telling second and third degree relatives our research supports other work (Suslak et al 1985, van Rijn et al 1997, Julian-Reynier et al 2000, Hughes et al 2002, Claes et al 2003 in that participants were more selective about who they told, mainly choosing to disclose to family members they felt emotionally close to or had some contact with. For example, one woman felt a particular responsibility to tell a certain cousin about the newly discovered risk of HD in their family, and although she was viewed as 'outside of the [close] family' she clearly felt some obligation to her:…”
Section: Theme 3: Who Is Family?supporting
confidence: 86%
“…Future studies would benefit from gaining access to the potentially differing accounts of different groups. Nevertheless, research relating to communication in families affected by balanced translocations (Suslak et al 1985, Wolff et al 1989, Ayme et al 1993 and recessive conditions such as cystic fibrosis (Denayer et al 1992a, 1992b, Fanos and Johnson 1995, Duster 1999, Ormond et al 2003 also suggests that complex communication issues are not limited to late-onset disorders.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In all focus groups, respondents acknowledged secrecy regarding illness in families, a finding that is widely reported in other studies regarding intrafamilial disclosures of genetic conditions [56,57,58,59,60,61] Likewise, most thought they would be willing to share this information with family members, but they based their decision to disclose on their relationship with the particular relatives and not on the basis of genetic risk [56,57,58,59,60, 62. ]…”
Section: Discussionmentioning
confidence: 60%
“…Unbalanced translocations can either be inherited or occur do novo, with neither parent having balanced rearrangement. However, many individuals may not be aware of their actual or potential carrier status as the decision to inform relatives is left to the known carrier individual 3. In a large retrospective review of 16 749 pregnant women undergoing midtrimester amniocentesis Chang et al 4 reported reciprocal translocation in 0.44%, the commonest type being balanced translocation (76%).…”
Section: Discussionmentioning
confidence: 99%